Impact of Sexual Cognition and Sexual Anxiety on the Mental Health of Married and Unmarried Population in India - Manish Kumar Jaisawal; Rajbala Kumari; Gaurav Kumar Rai (Journal of Psychosexual Health)
Background: Negative sexual cognition and sexual anxiety create a substantial amount of distress and guilt in an individual, which in turn can lead to reduced well-being. However, the impact of sexual cognition and sexual anxiety on mental health are less researched topics, especially in the Indian context. Aim: To investigate the effect of sexual cognition and sexual anxiety on mental health. Method: 124 participants of age range 18–35 years were recruited using purposive sampling method. Sexual Cognition Checklist, Sexual Anxiety Inventory, and Mental Health Inventory were used to assess sexual cognition, sexual anxiety, and mental health respectively. Results: Mental health was significantly negatively associated with sexual anxiety and negative sexual cognition. Also, a significant positive correlation was found between positive sexual cognition and mental health. Negative sexual cognition and sexual anxiety emerged as significant predictors, accounting for approximately 20% and 6% of the variance in mental health, respectively. Finally, an independent sample t -test suggests that males and females significantly differ in their level of sexual cognition, mental health, and sexual anxiety. Conclusions: Negative sexual cognition and sexual anxiety are associated with poor mental health while positive sexual cognition is associated with better mental health. Unmarried Indian women tend to experience more negative sexual cognition and sexual anxiety than married women.